CXCL14 regulates cell proliferation, invasion, migration and epithelial-mesenchymal transition of oral squamous cell carcinoma. Issue 1 (1st January 2019) - Rong, Liang; Wang, Lie; Shuai, Yi; Guo, Hongyan; Liu, Ke
Abstract: Oral squamous cell carcinoma (OSCC) is an aggressive malignancy which is the most common type of head and neck cancer. The study aimed to investigate the role of CXCL14 in cell proliferation, invasion, migration, and epithelial-mesenchymal transition (EMT) of OSCC and its potential mechanisms. In the present study, overexpression of CXCL14 was employed in TCA-8113 cells. Cell proliferation was detected using Cell Counting Kit-8 assay and flow cytometry. Scratch wound healing and Transwell assays were applied for the analysis of cell migration and invasion, respectively. Quantitative real-time polymerase chain reaction analysis was used to explore the mRNA expression of CXCL14 and PD-L1. Moreover, the protein expression levels of CXCL14, E-cadherin, N-cadherin, vimentin, PD-L1, NF-κB p65, and phospho-IκB-α (p-IκB-α) were examined by Western blot. The results revealed that the overexpression of CXCL14 was associated with suppressed proliferation of TCA-8113 cells coupled with decreasing the percentages of cells in the S phase. Moreover, the levels of cell migration and invasion were attenuated as well. Additionally, the expression level of EMT relative protein E-cad was increased notably, whereas N-cad and Vimentin were decreased. Importantly, the mRNA and protein expression of PD-L1, a crucial factor for OSCC, were lowered after overexpression of CXCL14. At the same time, the expression of NF-κB p65 and p-IκB-α was down-regulated significantly. Taken together, we speculate that CXCL14 inhibited OSCC cell proliferation, invasion, migration and EMT via suppressing PD-L1 expression and NF-κB mediated EMT, which indicated that CXCL14 may be an underlying target for OSCC treatment.